PENERAPAN TEKNIK PARAFRASE DENGAN PENGANDAIAN 180 DERAJAT BERBEDA DALAM PEMBELAJARAN MENULIS CERPEN - Laras, Mardwitanti (2014)
This research motivated by the fact that shows the student's lack of interest and ability in writing short stories. Writing short stories is considered as difficult by most of the student, especially on finding and expanding a topic into a whole stories. Therefore to apply a learning tehniques to write short stories in the form of Paraphrasing Tehniques with 180 Degrees Supposition. Formulation of problem in this research were: 1) how student's skill in writing short stories before and after the learning process by applying of Paraphrasing Tehniques with 180 Degrees Supposition in experiment class; 2) how student's skill in writing short stories before and after the learning process without applying of Paraphrasing Tehniques with 180 Degrees Supposition in control class?; are the any significant differences in student's skill in writing short stories in the experiment class and the control class? The purpose of this research itself is to describe the problems listed on the problems formulation. The type of this research is quasi-experiment using control group pretest-posttest design. The measuring instruments used during the research will be used as a success rate measurement of applying Paraphrasing Tehniques with 180 Degrees Supposition which is the result of the short stories written by the students. Population of this research are 8th grade students of SMP Negeri 15 Bandung with VIII-A students acting as the sample of experiment class and VIII-H acting as the sample of control class. Sample of each class consist of 33 students. Based on the result from hypothetical test by using SPSS 20.0, thitung score which taken from the average score gained from experiment class and control class is 7,175 > ttabel on significant level 95% and dk=64, it can be concluded that the result is 1,997. This result shows that the n-gain of experiment class and control class are significantly different from one and another. Therefore, it can be assumed that there are significant differences between the experiment class and control class after applying Paraphrasing Tehniques with 180 Degrees Supposition in learning to write short stories in experiment class.